Harmonisasi terhadap Peraturan Daerah No. 14 Tahun 2006 tentang Pengelolaan Pelestarian Kawasan Konservasi Laut Daerah dalam Perlindungan Pulau Pariwisata Kabupaten Indramayu - Kholik, Saiful; Khaeriyah, Imas (Jurnal Suara Hukum, 2019)
Inconsistency Regional Regulation No.14 of 2006 about marine conservation area of the island of Biawak, Gososng, which Cendekian provides protection but in fact failed to provide protection as evidenced by dredging island sandbar and cendekian conducted PT.Pertamina UP VI Balongan INDRAMAYU. The problem in this research How Formulation Policy Act No. 10 Year 2009 on the Indonesian Tourism with the Indramayu Regional Regulation No. 14 of 2006 regarding marine conservation area of the island of Biawak, Gososng, Cendekian And How Harmonization Act No. 10 of 2009 with the Indramayu Regional Regulation No. 14 of 2006 regarding formulation Act No. 10 Year 2009 on the Indonesian Tourism with the Indramayu Regional Regulation No. 14 of 2006 about marine conservation area of the island of Biawak, Gososng, Cendekian, the purpose of this research to understand and analyze the extent to which policy The findings of the community or field of law local governments about the environmental damage done by companies or individuals are not equal accordance with regional regulations in force, nor the Law in force so that the function of law in society indramayu not fit the mandate to establish a change and justice based Formulation public corporate criminal liability.Inskonsitensi happens to local regulation No.14 of 2006 makes no harmonized with the regulations of each other so that the impact of this inskonsistensi makes the sector particularly environmental law enforcement get uncertainties that result in coastal communities Indramayau.Conclusion Harmonization of regulations of the center and regions delivering the policy formulation of the rule of law area to comply with the regulations above in order to avoid inconsistency, the occurrence of this inconsistency resulted in the rule of law and justice for the indramayu, suggestion that the government should was nearly revise regulations related area, especially the government must dare to take action to give effect to the perpetrator deterrent effect rule-based running as well as possible.